The effect of bromhexine on mucosal immune response against avian coronavirus infectious bronchitis vaccine in chickens - Gholami-Ahangaran , M; Hjazi , A; Hussny, HA; Amir , AA; Abdulhussien Alazbjee , AA; Karimi-Dehkordi , M (Journal of the Hellenic Veterinary Medical Society, 2024)
Avian coronavirus infectious bronchitis (IB) is one of the most important and contagious disease in chickens, all over the world. Using of chemical compounds that improve the mucosal immune response to IB vaccine can increase resistance against the virus. To examine the effect of Bromhexine on the mucosal immune response against IB vaccine, 360 one-day broiler chicks were allocated to eight groups, randomly. Group one was the control group with no vaccine so that the group only used Bromhexine. Groups 2, 3, and 4 received IB vaccine for once, twice, and three times at the age of 5, 15, and 25 days, respectively. These groups received Bromhexine from 48 hrs before the vaccination to 24 hrs after receiving the vaccine in drinking water. Group five was the negative control group and did not receive Bromhexine and IB vaccine. Sampling in group five was at the age of 15 days. Groups six, seven, and eight were the main treatment control groups and received IB vaccine at the age of 5, 15, and 25 days without Bromhexine. The chickens were slaughtered 10 days after the vaccination and nose and trachea samples were collected and the mucus surface of respiratory was rinsed. Afterwards, specific immunoglobin A (IgA) level against IB vaccine in the respiratory mucus was measured through ELISA using chicken IgA specific antiglobulin. The results showed that the use of Bromhexine on the first vaccination had no effect on mucosal immune response. However, with the second and third vaccinations, antibody titter to IB vaccine was higher than chickens received vaccine without Bromhexin. It appears that using Bromhexine in booster IB vaccination can improve specific mucosal immune response.